First principle structural and electronic properties of Sr3Sb2 compound of the cubic Phase - Abdullah, Muhamad Hamad; Sedighi, Matin; Othman, Mazin Sherzad; Mahmodi, Behroz (Sulaimani Journal for Pure and Applied Sciences, 2015)
The structural and electronic properties of Sr3Sb2 at ambient and under hydrostatic pressure have been calculated using the full potential linear augmented plane wave (FP-LAPW) method. We calculated lattice constant, bulk modulus, the derivative of bulk modulus, cohesive energy, energy, band gap and density of state by using GGA96 method for exchange-correlation. Also, for calculating band structure we used GGA96 and EV-GGA on ambient and under hydrostatic pressure. The magnitude of the gap by GGA96 method is 1.51eV and by EV-GGA is 2.28eV. By fitting the data around the conduction band minimum and the valence band maximum, we find the effective mass of electron and hole of this compound
Keywords: DFT; Band structure; electronic properties; structural properties; effective mass